Hubungan Konsentrasi Ekstrak Daun Puring dengan Variabilitas Parameter Bioaktivitas - Haryanto Haryanto; Ainun Jariyah; Norita Norita; Nia Agustina; Rarah Maulidya Putri; Hastata Hastata; Naylha Salsabila Hs; Naylha Musdalifa Rabbani; Hanabila Putri; Husnul Khatimah; Najwa Nur Sahdrina (Asosiasi Riset Ilmu Kesehatan Indonesia, 2025)
The puring plant (Codiaeum variegatum), which has been known as an ornamental plant, apparently has significant therapeutic potential, supported by the presence of secondary metabolites such as flavonoids, tannins, saponins and alkaloids. Various modern studies report the biological activity of croton leaves, including anti-cholesterol, anti-hyperglycemia, antibacterial effects, and their use in biosurfactant formulations. However, studies on how varying extract concentrations influence bioactivity parameters quantitatively are still limited, especially in the context of dose-response relationships involving many biological parameters in one series of research. Therefore, this research was conducted to evaluate eight bioactivity parameters, namely PSM, SSSP, DSSP, SL, RO, SM, PSL, and ANA at croton leaf extract concentrations of 1%, 2%, and 4%. This research uses a laboratory experimental approach by extracting croton leaves through a maceration method using ethanol, then formulated in three concentration levels. Each parameter was analyzed quantitatively to observe the pattern of changes in biological response to variations in the dose administered. The results showed that most of the PSM, SSSP, DSSP, SL, and PSL parameters showed an optimum response at a concentration of 2%, which indicates that there is a most effective dose point before a decrease in activity occurs at the highest concentration. In contrast, several parameters such as RO, SM, and ANA showed a more fluctuating response, even the ANA parameter gave the highest value at a concentration of 4%, indicating that certain activities require higher compound levels to be achieved. In general, the response pattern found was not linear, but instead formed an optimum curve typical of the bioactivity of plant extracts. These findings confirm that determining dosage is very important in the use of croton leaf extract, both for pharmacological purposes and for the formulation of natural ingredient-based products.